Flow cytometric osmotic fragility test and eosin‐5’‐maleimide dye‐binding tests are better than conventional osmotic fragility tests for the diagnosis of hereditary spherocytosis - Arora, R. D.; Dass, J.; Maydeo, S.; Arya, V.; Radhakrishnan, N.; Sachdeva, A.; Kotwal, J.; Bhargava, M. (International journal of laboratory hematology, 2018)
Introduction Hereditary spherocytosis (HS) is the most common inherited hemolytic anemia with heterogeneous clinico‐laboratory manifestations. We evaluated the flow‐cytometric tests: eosin‐5’‐maleimide (EMA) and flow‐cytometric osmotic fragility test (FOFT) and the conventional osmotic fragility tests (OFT) for the diagnosis of hereditary spherocytosis (HS). Methods One hundred two suspected HS patients underwent EMA, FOFT, incubated OFT (IOFT), and room temperature OFT (RT‐OFT). In addition, 10 cases of immune hemolytic anemia (IHA) were included, and performance of the above 4 tests was evaluated. For EMA and FOFT, 5 normal controls were assessed together with the patients and cutoffs were calculated using receiver‐operator‐characteristics curve (ROC) analysis. Results The best cutoff for %EMA decrease was 12.5%, and for FOFT, %residual red cells (%RRC) was 25.6%. The sensitivity and specificity of RT‐OFT was 62.06% and 86.3%, respectively, while that of IOFT was 79.31% and 87.67%, respectively. Both flow cytometric tests performed better. Sensitivity and specificity of EMA was 86.2% and 93.9% respectively, and that of FOFT was 96.6% and 98.63%, respectively. The combination of the FOFT with IOFT or EMA dye‐binding test yields a sensitivity of 100%, but with EMA, it had a higher specificity. Hb/MCHC was a predictor of the severity of the disease while %EMA decrease and %RRC did not correlate with severity of the disease. Conclusion Flow‐cytometric osmotic fragility test is the best possible single test followed by EMA for diagnosis of HS. A combination of FOFT and EMA can correctly diagnose 100% patients. These tests are likely to replace conventional OFTs in future.